Teacher and students’ Perceptions on Interactive Multimedia in teaching English at Senior High School - Yola Audina Saputri (Prodi Teknologi Pendidikan, 2022)
This study aims to see how the teacher and students’ perception on Interactive Multimedia in teaching English at Senior High school in Padang Pariaman. This study uses descriptive qualitative as the method within the interview as an instrument for this research. So, the researcher took one English teacher and 5 eleventh-grade students as participants to be interviewed. The results of this study indicate that there is a misunderstanding of the concept of interactive multimedia used by the teacher and the students. The teacher already use multimedia in teaching english, but the multimedia used did not include interactive multimedia. However, based on the results of interviews, the teacher and the students gave positive responsd to the use of multimedia in the teaching and learning process of english because it is interesting so that the students are interested and focused on learning. By using multimedia, it is easier for the teacher to convey the material and explain the material systematically in supporting the teaching and learning process in the classroom.